2022
DOI: 10.3390/life12030373
|View full text |Cite
|
Sign up to set email alerts
|

Evaporation Patterns of Dextran–Poly(Ethylene Glycol) Droplets with Changes in Wettability and Compatibility

Abstract: The dextran–PEG system is one of the most famous systems exhibiting phase separation. Various phase behaviors, including the evaporation process of the dextran–PEG system, have been studied in order to understand the physicochemical mechanism of intracellular phase separation and the effect of condensation on the origin of life. However, there have been few studies in dilute regime. In this study, we focused on such regimes and analyzed the pattern formation by evaporation. The specificity of this regime is th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…For other polymers it has been observed, that increased solid concentrations of these type of excipients, led to phase separation and increased aggregation in the protein rich phase [ 53 , 54 ]. Furthermore, this phase separation during sessile droplet drying, caused by DEX and other species of high molecular weight, has been elucidated recently [ 55 ]. In the latter work, the authors showed that DEX has a tendency to accumulate at the contact line between droplet and surface, whereas other species of high molecular weight, like polyethylene glycol, rather show a tendency to stay at the droplet centre [ 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…For other polymers it has been observed, that increased solid concentrations of these type of excipients, led to phase separation and increased aggregation in the protein rich phase [ 53 , 54 ]. Furthermore, this phase separation during sessile droplet drying, caused by DEX and other species of high molecular weight, has been elucidated recently [ 55 ]. In the latter work, the authors showed that DEX has a tendency to accumulate at the contact line between droplet and surface, whereas other species of high molecular weight, like polyethylene glycol, rather show a tendency to stay at the droplet centre [ 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…[221]. A simple bio-mimetic colloidal solution, dextran-polyethylene glycol, deserves attention for examining the phase separation in the drying droplet by tuning their initial concentrations, leading to a change of wettability and compatibility [222]. Recently, a concentration-driven phase transition has been found when diluted human blood droplets and a high concentration of BSA droplets are dried under ambient conditions [31].…”
Section: A Fundamental Understanding Of Bio-colloidal Drying Dropletsmentioning
confidence: 99%
“…Nevertheless, another possibility could be through macromolecular self-assembly, which was absolutely essential to the origins of life [54][55][56]. However, macromolecular self-assemblies could take many forms, for example droplets [57,58], crystals [59,60], fibers [61,62], or even more complex architectures [63,64]. However, one type of macromolecular selfassembly likely to have been relevant for origins of life were primitive compartments, also known as protocells, which themselves may have eventually evolved into modern cells (although it is not a strict requirement) [65][66][67].…”
Section: Membraneless Polyester Protocellsmentioning
confidence: 99%